Apport des SIG dans l'étude de la qualité des eaux souterraines par la méthode d'analyse hiérarchique des Procédés (AHP) dans la région Nord-ouest d'Elouad - عطية, محمد أسامة; زين, عبد الكريم (university of Eloued جامعة الوادي, 2019)
For a long time, water was a natural product and the gift of God was free and easy to use. So to speak, it was of great value. The region of El Oued (SE Algeria) is characterized by the superposition of three aquifer layers; it is from top to bottom, the superficial aquifer, the aquifer of the terminal complex and the aquifer of the continental intercalary . Due to the high pollution and the high mineralization of the water table, the population exploits the aquifers of the terminal complex to meet their needs, but its quality is still in question. The study of the water quality of the aquifer of the terminal complex for the supply of drinking water (AEP) shows that they are not drinkable, in reference to the standards of the World Health Organization (WHO) and the Algerian standards for drinking water. They are highly mineralized. As for its quality for irrigation, based on the Riverside standards, they settle in the class of mediocre waters. The main objective of this study is to establish a diagnosis of groundwater quality in the El Oued region, based on a geographical information system (GIS). The physico-chemical quality analysis included 45 samples taken from the holes of the terminal aquifer in the study area, used for human consumption. The results obtained showed that the water of the sheet in question has a varied quality of medium to poor. This concerns more particularly the pH, the electrical conductivity (mineralization), as well as the concentration of the major elements. This can probably be due to the proximity of agricultural land and the intensive use of fertilizers in farming practices (the region devoid of intensive industrial activity). To this end, continuous assessment of water quality is imperative and treatment to reduce deterioration of water quality and eliminate health problems may be necessary.
مذكرة ماستر تخصص في منشئات الري
Keywords: Water quality - method OF Hierarchical analysis of prosses (AHP) - Complex final layer; نوعية المياه – طريق التحليل الهرمية – الطبقة النهائية المعقدة